Pengaruh Persepsi Pelaku Usaha Mikro Kecil dan Menengah Tentang Penyusunan Laporan Keuangan UMKM Berdasarkan SAK – EMKM Terhadap Penggunaan Informasi akuntansi perpajakan (Studi Kasus Pelaku UMKM di Desa Perkebunan Ramunia) - Putri, Wan Hafizah Ainun Syah; Hafsah, Hafsah (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this research is to determine whether the Perception of Micro, Small, and Medium Enterprises (MSMEs) Regarding the Preparation of Financial Statements for MSMEs Based on SAK-EMKM Has an Influence on the Use of Tax Accounting Information. The research approach used by the researcher is associative quantitative research. The population in this study consists of 100 Micro, Small, and Medium Enterprise operators in the Ramunia Plantation Village. Meanwhile, the sample used in this study is 99 micro, small, and medium enterprise operators. The sampling technique used in the research is random sampling. The results of the research based on the regression equation above can analyze the influence of each independent variable on the use of accounting information, namely: the constant figure of 13.320 states that if the independent variable, namely the Perception of Micro, Small, and Medium Enterprises, is in a constant or unchanged state, then the Use of Accounting Information (Y) is 13.320. Based on the research, it can be concluded that the hypothesis testing partially for each independent variable against the dependent variable is as follows: The significance value for the Perception of Micro, Small, and Medium Enterprises is 0.872. This value is smaller than the significance level = 0.05. Based on the criteria above, the value of 0.872 > 0.05, so H0 is accepted and Ha is rejected, meaning that the Perception of Micro, Small, and Medium Enterprises does not affect the use of tax accounting information. This lack of influence is caused by the inability to recognize and interpret understanding of tax accounting information properly, the uncertainty of laws and taxes that often change, and the non-compliance of tax information.